Consultation-Liaison Psychiatry: A Step toward Achieving Effective Mental Health Care for Medically Ill Patients - Siddharth Sarkar; Swarndeep Singh (Indian Journal of Psychiatric Nursing)
Consultation-liaison (CL) psychiatry is at the interface of psychiatry and other medical/surgical specialties and deals with providing clinical services or care to medically ill patients seen at the medical or surgical inpatient or outpatient departments. This review article aims to highlight the scope of CL psychiatry practice and the need for having effective CL psychiatry clinical services, with special emphasis on discussing how developing CL psychiatry services could help in overcoming existing barriers in the delivery of effective mental health care in the general hospital or primary health care settings. An electronic literature search was performed using the PubMed and Google Scholar search engines for selecting papers related to theme of CL psychiatry and effective mental health care or treatment. The CL psychiatry services improve the overall course and prognosis of both physical and mental health disorders in patients admitted under the medical or surgical hospital wards, with a reduction in length of stay, rehospitalization rates, and total health costs incurred to the medical systems. It can help in bridging the existing mental health treatment gap by overcoming existing barriers such as poor recognition of mental health problems, inadequate treatment, and high mental illness-related stigma.